2015
DOI: 10.3109/09513590.2015.1047448
|View full text |Cite
|
Sign up to set email alerts
|

In vitro-assessment of putative antiprogestin activities of phytochemicals and synthetic UV absorbers in human endometrial Ishikawa cells

Abstract: Critical steps of embryo implantation are controlled by progesterone. These processes can be interrupted by progesterone receptor (PR) antagonists, e.g. drugs used for abortion. Antiprogestin effects induced by natural compounds and environmental chemicals have been rarely addressed. In our in vitro study, we investigated putative antiprogestin activities of the plant compounds apigenin (API) and trans-ferulic acid (t-FA) as well as the UV absorbers octyl methoxycinnamate (OMC) and 4-methylbenzylidene camphor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…At present, CC remains the first-line drug for ovulation induction, with ovulation rates of 75% to 80%,9 but recent studies have shown that a considerable proportion of patients did not get desirable pregnancy outcomes after CC treatment 10,11. In the normal ovulation process, estrogen and progesterone play obvious regulatory roles, and CC has anti-estrogenic effects, but its exact mechanism has not been fully clarified yet 12. It has previously been reported that13,14 the chemical structure of CC is similar to that of estrogen, so it is capable of binding estrogen receptor (ER) and then competitively occupying the hypothalamic ER to inhibit the negative feedback of endogenous estrogen to the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…At present, CC remains the first-line drug for ovulation induction, with ovulation rates of 75% to 80%,9 but recent studies have shown that a considerable proportion of patients did not get desirable pregnancy outcomes after CC treatment 10,11. In the normal ovulation process, estrogen and progesterone play obvious regulatory roles, and CC has anti-estrogenic effects, but its exact mechanism has not been fully clarified yet 12. It has previously been reported that13,14 the chemical structure of CC is similar to that of estrogen, so it is capable of binding estrogen receptor (ER) and then competitively occupying the hypothalamic ER to inhibit the negative feedback of endogenous estrogen to the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…The level up- and down-regulation of sex hormone receptors are associated with sex hormones and related cytokines. The endometrium, as the target tissue of estrogen and progesterone, has corresponding estrogen receptors (ERs) and progesterone receptor (PRs) 4. The ERα and ERβ levels of eutopic endometrium of normal women of childbearing age vary with the menstrual cycle, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The absorbance at 570 and 600 nm were measured by microplate photometer. The viability of the cells was then calculated by using the formula in a previous study 25 . Viability of the cells=(ODtreated—ODblank/ODcontrol—ODblank)×100%.…”
Section: Methodsmentioning
confidence: 99%